Budgets and financial management in higher education - Barr, Margaret J. (Jossey-Bass, 2018)
This book provides an understanding of the basics of budgeting and fiscal management in higher education. Defines the elements of a budget, the budget cycle, and the steps for creating a budget. Suggests ways of avoiding common pitfalls and problems of managing budgets.....